The Concept of Management of the Heart (Qalbu) in the style of the Prophet Muhammad SAW in Business Ethics - Satria Avianda Nurcahyo (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
The heart is like a mirror. As long as the mirror is clean from dirt and stains, everything can be seen in it. But if the mirror is covered with blemishes, and nothing can remove the blemishes from it and polish it, then the mirror is spoiled. The mirror can no longer be cleaned and polished. Management of the Heart is understanding yourself and being willing and able to control yourself after understanding who you are. And the place to truly understand who this self is is in the heart, the heart that shows the character and true self. The heart that makes this self capable of achievement is only because of Allah. In the concept of heart management, every desire, feeling, or impulse that comes out of a person's intentions will be filtered to give birth to something good and noble and full of benefits. Not only for the life of the world but also for the afterlife. More than that, with good heart management, a person can also respond to all forms of action or actions from outside himself, both positively and negatively, proportionally. Like a tower, the heart has many doors. Like a mirror, the heart can absorb and reflect every image that comes to it. Then the influence of the object will enter the heart, and leave an imprint in it through the external means, namely the five senses, or through the inner means, namely fantasy, passion, anger, and morals that form naturally. Development of conscience with the light of faith and belief. On the other hand, the darkness of the heart is due to the beautiful picture of the world hanging over his heart.